Prosthetic challenges in patients submitted to oncological treatment of the head and neck: An integrative review (Research, Society and Development, 2023)
Objective: To review the literature on the challenges that will be encountered for the oral rehabilitation of patients undergoing oncological treatment of the head and neck. Materials and Methods: An integrative review was carried out in the SciELO, PubMed, VHL and book databases, using articles from the last 10 years with inclusion and exclusion criteria. Results: Head and neck cancer accounts for 3% to 5% of malignant neoplasms. Treatment may involve surgical resection, chemotherapy, radiotherapy, hormone therapy or a combination of more than one form of treatment. There may be side effects to these. Oral rehabilitation in patients undergoing chemotherapy and radiotherapy is different; in chemotherapy it has severe repercussions related to the systemic and oral level, since the tissue response time is related to cell renewal mechanisms and in radiotherapy the placement of implants has proven to be a viable alternative when analyzing the risk factors. The literature has cited successful cases in the placement of implants in cancer patients with good success rates with endoosseous implants and prostheses on implants, showing positive efficacy in osseointegration. Conclusion: Oral rehabilitation for patients undergoing head and neck cancer treatment is still a challenge for dentists, since this type of cancer, as well as its treatment, have different characteristics for each patient. It is imperative that the dental surgeon rehabilitate cancer patients to restore their health, aesthetics and self-esteem.